Kinerja Guru dan Permasalahannya - Atik Likai Tanjua; Desy Eka Citra Dewi; Nur Puspasari; Hilman Nugraha; Deli Meylindo (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
Teacher performance is one of the determining factors in the success of education and the quality of learning in schools. Although many efforts have been made to improve the quality of teaching, various problems faced by teachers often hinder this achievement. These problems can come from internal factors such as motivation, job satisfaction, and professional skills, as well as external factors such as education policies, school facilities, and social support. This study aims to analyze the factors that influence teacher performance, identify problems often faced by teachers, and provide recommendations to improve the quality of their performance. This study uses a library research approach, by reviewing various relevant literature, both from books, articles, research reports, and related policy documents. The results of the study indicate that internal factors that influence teacher performance include motivation, level of job satisfaction, and the quality of professional skills possessed by teachers. Teachers who feel appreciated, have high motivation, and are satisfied with their work tend to have better performance. In addition, professional skills that are continuously updated through training and development are important factors in improving the quality of teaching. Meanwhile, external factors such as inflexible education policies, lack of adequate facilities, and low teacher welfare conditions also worsen teacher performance in the field. Policies that focus too much on exam results or high administrative burdens often make teachers unable to focus on developing the quality of learning.